Aenigma Omnibus? The Transatlantic Late Humanism of Zinzendorf and the Early Moravians. (1st August 2019) - Keeline, Thomas; McManus, Stuart
This article uncovers a hitherto underappreciated aspect of transatlantic cultural history: Moravian late humanism, and its relationship to contemporary intellectual currents in the Americas and the broader Republic of Letters in the age of Benjamin Franklin. To date, the Moravians have attracted the attention of scholars for their novel theological views on gender and sexuality, their unique approach to reconciling piety with profit, their missionary efforts among native populations, their musical culture and their rejection of slavery. Their interactions with the world of transatlantic and global late humanism, however, have not been studied in any systematic way. The present analysis opens and closes with a remarkable but almost unknown Latin oration, delivered in Philadelphia in 1742 by Nicolaus Ludwig von Zinzendorf, to an audience provided with printed copies commissioned from the Franklin Press. A critical edition and an English translation of this work are provided in an appendix. In our article we examine the original European genesis and subsequent transatlantic context of Zinzendorf's oration, tracing its development from a formal theological apologia into a quasi-legal statement of the count's commitment to Moravian values, expressed in an erudite allusory language which left its listeners bemused. As our investigation shows, however, the confusion of the Philadelphia worthies who gathered to hear Zinzendorf's oration cannot be put down to a lack of cultural awareness among the leading missionaries and settlers from Germany and Denmark, many of whom partook fully in the contemporary culture of late humanism, both before and after they crossed the Atlantic. Through detailed reconstructions of their educations, correspondence networks, reading habits and note-taking practices, we show the richness of the Moravians' transatlantic culture of late humanism, which ran the gamut from Ciceronian oratory to pious poetry in learned languages. Basing our argument on a little-known body of archival and printed sources in Latin, German, English and indigenous languages, we argue that Moravian late humanism had a significant impact on the development and expression of the Moravian church's unique theology, its missionaries' study of native languages and their interactions with other groups in the Atlantic world. In so doing, we also place the Moravians in the context of contemporary intellectual life in New England, the Caribbean, Europe and the Catholic world. [An Index of Manuscripts and Archival Documents has been provided on the final page of this article.]